Circular RNAs in the Regulation of Oxidative Stress - Zhang, Yao; Chen, Yu; Wan, Yue; Zhao, Yueshui; Wen, Qinglian; Tang, Xiaolong; Shen, Jing; Wu, Xu; Li, Mingxing; Li, Xiang; Li, Jing; Li, Wanping; et al. (Frontiers in Pharmacology, 2021)
Oxidative stress caused by an imbalance between the production and elimination of reactive metabolites and free radicals can lead to the development of a variety of diseases. Over the past years, with the development of science and technology, circular RNA (circRNA) has been found to be closely associated with oxidative stress, which plays an important role in the process of oxidative stress. Currently, the understanding of circRNAs in the mechanism of oxidative stress is limited. In this review, we described the relationship between oxidative stress and circRNAs, the circRNAs related to oxidative stress, and the role of circRNAs in promoting or inhibiting the occurrence and development of diseases associated with the oxidative stress system.